Testing of Integrated Sales Information Systems On UD. Remaja Bumi Raya Based on Black Box Testing with Equivalence Partitioning Method - Muhammad Arifin; Fery Ariyana; Anteng Widodo (APTIKOM SUMSEL, 2022)
UD. Remaja Bumi Raya is a business in the field of selling agricultural materials that provides various types of fertilizers and agricultural medicines. This UD has developed a sales information system that is integrated into stock management and transactions connected between branches so that owners can find out the number of stocks and transactions from each branch in real time. Black Box testing is an application test that covers the outer side of a software, from the display to the input action, while the Equivalence Partitioning method is a testing method in the aspect of input validation from the Valid Class side, observation of input content and input accuracy, so that the error side of the application being tested can be known. The purpose of this study is to determine the quality and errors in the Integrated Sales Information System at UD. Remaja Bumi Raya by using Black Box Testing with the Equivalence Partitioning method. The results of the study show that the selling information system is feasible to implement because it has a minimal error rate. The use of Black Box Testing with the Equivalence Partitioning method can be used to test the software before it is implemented.